Highly conductive hybrid carbon nanotube fibers: Strategies and future directions for replacing copper with next-generation conductors - Jo, Sungchan; Mikhalchan, Anastasiia; Hong, Seungki; Kim, Soyeon; Kim, Seo Gyun; Kim, Seung Min; Kim, Dae-Yoon; Ku, Bon-Cheol; Vilatela, Juan Jose; Hwang, Jun Yeon (Pergamon Press Ltd., 2025)
Carbon nanotube (CNT) fibers represent a promising alternative to conventional copper-based conductors. This review summarizes the advancements achieved over the past decade in the large-scale fabrication of wire-shaped CNT assemblies for macroscopic cables, and discusses strategies to achieve electrical properties comparable to copper through doping or hybridization. Two primary fiber fabrication methods, wet spinning from acidic CNT solutions and dry spinning from CNT aerogels, are analyzed in terms of bulk properties, constituent CNT characteristics, and alignment degree. The analysis reveals that when CNT fibers have sufficiently high alignment degree (FWHM approximate to 7 degrees) and CNT aspect ratio (>4400), their electrical conductivity converges to approximately 2 x 10(6) S/m. This value aligns with both the conductivity of CNT bundles and the theoretical conductivity of ideally structured CNT fibers as macroscopic CNT assemblies. Notably, wet-spun fibers exhibit a relatively high conductivity, reaching a maximum of 11.2 x 10(6) S/m, attributed to intercalated residual dopants. Therefore, doping is an effective approach to overcome the intrinsic electrical conductivity limitations of CNT fibers. The mass-normalized conductivity (specific electrical conductivity) of CNT fibers can surpass that of copper through optimized doping techniques. However, this presents new challenges related to dopant selection, uniform intercalation, and intercalant stability under ambient conditions. Alternatively, incorporating a small mass fraction of metals into CNT fibers, coupled with proper interfacial control and metal crystallization, results in a specific electrical conductivity exceeding that of copper by 50 %, while maintaining exceptional bending tolerance. Whether enhanced by dopants, metals, or organic species, CNT fibers demonstrate an exceptional combination of high thermal conductivity, ampacity, electrical conductivity, and mechanical properties, solidifying their potential as next-generation electrical conductors.